Automatic detection of prolongations and repetitions using LPCC - Chee, L. S.; Ooi, Chia Ai; Hariharan, M.; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/